Pariwisata sebagai Alat Soft Power Diplomacy dalam Hubungan Internasional - Danuwijaya, Try; Manglili, Gita Bhayangkari (Universitas Pendidikan Muhammadiyah Sorong, 2024)
Tourism is one of the subjects that can be researched in International Relations as well as tourism as a tool of soft power diplomacy. Tourism is a powerful instrument in diplomacy that is able to promote a positive image of a country. One of the key aspects of tourism as soft power diplomacy is its ability to build bridges between nations through cultural exchanges and recreational experiences. The concept of tourism as part of soft power is a strategy used by a state to influence another person or another country through cultural, economic, and political appeal, without using military or economic force. Countries with interesting natural, historical, and cultural wealth can use tourism as a public diplomatic instrument to promote the country and enhance international cooperation.